(untitled) (Bangladesh Journal of Agricultural Research, 2008)
The experiment was conducted to find out suitable formulation for preparation of bael beverage. The beal pulp was analyzed for its composition and different formulations of beverages were prepared using varying proportions of bael pulp and different concentrations of thickening agents, such as sodium alginate, xanthane gum, and CMC. The prepared bael beverages were packed in glass bottle with lug cap. The bael pulp showed 61.9% moisture, 32% TSS, Vitamin C content 8.89mg/100mg, and acidity 0.35%, reducing sugar 5.08%, non-reducing sugar 12.05%, total sugar 17.13%, mucilage 4.92%, and pH 4.3 (with titrable acidity 0.5%). The glass packed beverages were stored at room temperature for a period of 150 days and evaluated for their keeping quality at an intervals of 30 days. It was revealed that the sedimentation was minimized by using CMC and found to be more effective for reducing the sedimentation than xanthae and sodium alginate. A five-member taste panel opined that formulation T1 (16% bael pulp = 0.2% CMC + 0.28% citric acid + 11.07% sugar + 0.06% KMS) had the highest overall acceptability among other treatments. Bangladesh J. Agril. Res. 32(4) : 573-586